2016
DOI: 10.1039/c6ra16739j
|View full text |Cite
|
Sign up to set email alerts
|

Visible light driven efficient N and Cu co-doped ZnO for photoinactivation of Escherichia coli

Abstract: N and Cu co-doped ZnO shows outstanding antibacterial activity for E. coli inactivation under visible light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 64 publications
2
27
0
2
Order By: Relevance
“… 44 46 Absolute cell death occurs probably by reactive oxygen species mechanism due to the synergetic effect of both metallic Cu clusters and ZnO in the case of E. coli , as already confirmed by Yu et al 46 We attribute this greater inhibitive effect for E. coli than that for B.cereus to the difference in cell-membrane structures, as supported by Yu et al 46 An additional advantage of Cu 9,18 @ZnO reported here is that the synthetic procedure is very simple and consumes less time and energy. The antibacterial activity could further be activated with the application of visible light, as reported by Gupta et al, 45 wherein the Cu plasmon is expected to play a major role along with ZnO, which will be investigated in the near future.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“… 44 46 Absolute cell death occurs probably by reactive oxygen species mechanism due to the synergetic effect of both metallic Cu clusters and ZnO in the case of E. coli , as already confirmed by Yu et al 46 We attribute this greater inhibitive effect for E. coli than that for B.cereus to the difference in cell-membrane structures, as supported by Yu et al 46 An additional advantage of Cu 9,18 @ZnO reported here is that the synthetic procedure is very simple and consumes less time and energy. The antibacterial activity could further be activated with the application of visible light, as reported by Gupta et al, 45 wherein the Cu plasmon is expected to play a major role along with ZnO, which will be investigated in the near future.…”
Section: Resultsmentioning
confidence: 96%
“…A recent antibacterial study of E. coli , Staphylococcus aureus , and Streptococcus pyogenes by Bhuyan et al 44 using pure and Cu-doped ZnO NPs showed that Cu-doped ZnO NPs have superior antibacterial action than that of pure ZnO NPs. In another study by Gupta et al, 45 on exposing the E. coli cells to N and Cu co-doped ZnO NPs under visible light irradiation, E. coli becomes inactive. The synergistic antibacterial effect of Cu@T-ZnO nanocomposites for both Gram-negative and Gram-positive bacteria was shown by Yu et al 46 Most importantly, the authors have positively proven them to have significant potential as bactericidal agent, 7 exemplifying a biocidal action of these particles against E. coli ATCC-25922 and Bacillus cereus ATCC-10876.…”
Section: Introductionmentioning
confidence: 97%
“…In a recent study of Gupta et al, N and Cu co-dopants narrow the bandgap of ZnO NPs effectively [135]. Figure 6a shows the Tauc plots of the Kubelka-Munk function vs photon energy for ZnO NPs, and Cu-doped ZnO NPs with 0.5%, 1.5%, 2.5% and 5.0% Cu, denoting as Cu0.5Z, Cu1.5Z, Cu2.5Z and Cu5.0Z, respectively.…”
Section: Metal/non-metal Co-dopantsmentioning
confidence: 94%
“…Figure 6c reveals that the (N, Cu) co-doped Cu5.0NZ exhibits a higher absorbance than Cu5.0Z in the visible light region. This is due to the synergistic action of both Cu 2+ and N dopants in Cu5.0NZ during the photoexcitation process [135]. Similarly, synergistic effects of both Mn 2+ and N dopants also enhance the absorption of ZnO nanofibers in the visible-light region [136].…”
Section: Metal/non-metal Co-dopantsmentioning
confidence: 99%
“…This method includes sampling of the bacterial solution and its serial dilution to visualize the countable number of colonies on the solid growth media. CFU/mL is counted by the given formula trueCFU/mL=normalnnormalunormalmnormalbnormalenormalr4ptnormalonormalf4ptnormalcnormalonormallnormalonormalnnormalinormalenormals4pt(normalfnormalonormalr4pt1001.69998pt1.69998ptμnormalL4ptnormalsnormalanormalmnormalpnormallnormale)4ptnormaldnormalinormallnormalunormaltnormalinormalonormaln×normalvnormalonormallnormalunormalmnormale4ptnormalonormalf4ptnormaltnormalhnormale4ptnormalsnormalanormalmnormalpnormallnormale4ptnormalpnormallnormalanormaltnormalenormald4pt()mL …”
Section: Recent Advancement In the Area Of Disinfection Researchmentioning
confidence: 99%